Adsorptive Removal and Regeneration Study of Biochanin A: An Endocrine Disruptor - Kaur, Kamalpreet (My University, 2015)
Phytoestrogens are produced by plants and mimic the hormone estrogen, and act as Endocrine Disruptors (EDCs). Though prevalence of phytoesterogens in water has been documented, few methods are available for the removal of phytoestrogens from water. In this study the removal of phytoestrogen Biochanin A was attempted from water with the help of adsorption method. The adsorbent materials used were bentonite, chitosan and granular activated carbon. The maximum removal of 98.9% at 5 mg/L with 1.5 mg/g was observed in granular activated carbon. The maximum removal with chitosan and bentonite was 46.1% and 44.2% respectively. The adsorption spectra of biochanin A onto granular activated carbon were studied using different parameters like temperature, pH, concentration of adsorbate and adsorbent. The adsorption study, adsorption isotherm and regeneration study were also carried out. The optimum pH and temperature for adsorption were found to 6 pH and 25°C. The adsorption isotherm models were applied to study nature of adsorption. The equilibrium data were perfectly represented by the Langmur isotherm with R2 of 0.9515, showing homogeneous adsorption of biochanin A to granular activated carbon and followed second order kinetics. The active carbon was characterized by Fourier transform infrared spectrophotometry. The granular activated carbon can be regenerated by reversing the adsorption of biochanin A on granular activated carbon, making it as good and inexpensive adsorbent for removal of biochanin A.
M.Sc. (Biotechnology)
Keywords: Phytoestrogens; endocrine; DBT